Greece : Background Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This Background Paper reviews economic developments in the real economy and the labor market of Greece during 1990-95. It presents the calculation of an index of coincident economic indicators, which is used to gauge the strength of the recovery. The paper highlights that in 1994, Greece's external accounts strengthened considerably: the current account deficit improved to near-balance reflecting strong invisible receipts (mostly tourism), and substantial capital inflows-following the successful handling of the speculative attack against the drachma in May 1994-boosted official reserves to a record USD 16.5 billion at end-June 1995.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet